Synthesis and antimalarial activity of N-benzylated (N-arylcarbamoyl)alkylphosphonic acid derivatives. Issue 23 (1st December 2016) - Adeyemi, Christiana M.; Faridoon,; Isaacs, Michelle; Mnkandhla, Dumisani; Hoppe, Heinrich C.; Krause, Rui W.M.; Kaye, Perry T.
Graphical abstract: Abstract: A series of novel and readily accessible N -benzylated ( N -arylcarbamoyl)alkylphosphonate esters and related compounds have been prepared as potential antimalarial agents. Bioassays reveal that some of these compounds exhibit promising activity against Plasmodium falciparum, and exhibit no significant growth inhibition of HeLa cells.